Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Lutter contre les violences conjugales : féminisme, travail social, politique publique - Herman, Elisa; Lagrave, Rose-Marie (Presses universitaires de Rennes, 2018)
Comprendre les violences faites aux femmes dans le couple c'est aussi analyser les luttes, les politiques publiques et les actions concrètes déployées en France aujourd'hui. Ce livre prend appui sur une enquête ethnographique menée auprès d'associations spécialisées (souvent membres de la Fédération nationale solidarité femmes), de femmes victimes, de professionnels de nombreuses institutions concernées (justice, police, travail social...) et de personnalités politiques et universitaires actifs sur ces sujets. S'adressant aux universitaires ainsi qu'aux professionnels, l'ouvrage décrit la construction de la cause des violences conjugales, ainsi que les politiques publiques mises en œuvre, dans une démarche sociohistorique. Il met ainsi en lumière la porosité des espaces militant, universitaire et institutionnel. L'analyse des carrières militantes et professionnelles, la prise en compte des parcours des femmes rencontrées et du contexte du nouveau management public structurant l'action publique, enrichissent la compréhension du travail social féministe mis en œuvre dans les structures d'accueil et d'hébergement des femmes victimes de violences conjugales et de leurs enfants. Cette recherche sociologique éclaire alors des engagements féministes professionnels trop peu connus, face au paradoxe d'un intérêt politique fort pour lutter contre des violences masculines toujours persistantes.
Keywords: 2000 à aujourd'hui; 2010-2019; cours; cycles supérieurs; discipline; fem7000; histoire et politique; périodes historiques; sciences humaines; thématiques; travail social; violences; violences conjugales

“Me Too”: Epistemic Injustice and the Struggle for Recognition - Jackson, Debra L. (Feminist Philosophy Quarterly, 2018)
Congdon (2017), Giladi (2018), and McConkey (2004) challenge feminist epistemologists and recognition theorists to come together to analyze epistemic injustice. I take up this challenge by highlighting the failure of recognition in cases of testimonial and hermeneutical injustice experienced by victims of sexual harassment and sexual assault. I offer the #MeToo movement as a case study to demonstrate how the process of mutual recognition makes visible and helps overcome the epistemic injustice suffered by victims of sexual harassment and sexual assault. I argue that in declaring “me too,” the epistemic subject emerges in the context of a polyphonic symphony of victims claiming their status as agents who are able to make sense of their own social experiences and able to convey their knowledge to others.
Keywords: #metoo; 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; cycles supérieurs; discipline; fem9000; harcèlement sexuel; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; philosophie féministe; périodes historiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éthique